Strategic sill pillar design for reduced hanging wall overbreak in longhole mining - Chen, Tuo; Mitri, Hani S. (International journal of mining science and technology, 2021)
Steeply dipping, vein and tabular orebodies are traditionally extracted with longitudinal retreat mining methods such as Eureka and Avoca in a bottom-up sequence with delayed backfill. To increase productivity, sill pillars in the orebody are used to separate mining zones thus allowing production to take place simultaneously in two or more zones. While such mining methods are productive, they may be accompanied with high volumes of hanging wall overbreak causing significant unplanned ore dilution. In this work, it is shown through a mine design case study of a narrow vein deposit that a sill pillar could also play a significant role in limiting hanging wall overbreak. To demonstrate the role of sill pillar, a novel numerical modelling scheme is proposed to account for progressive stope wall overbreak. A numerical modelling approach of element death and rebirth is developed to allow for the detected stope overbreak to be immediately removed and replaced with backfill material before upper-level stope extraction. It is further shown that the average overbreak volume could be reduced by as much as 33% when the sill pillar is strategically placed in the lower half of a mine plan.